Racial and Ethnic Postoperative Outcomes after Surgery: the Hispanic Paradox - Eguia, Emanuel (J Surg Res, 2018)
BACKGROUND: The Hispanic population in the United States have previously been shown to have, in some cases, better health outcomes than non-Hispanic whites (NHW) despite having lower socioeconomic status and higher frequency of comorbidities. This epidemiologic finding is coined the Hispanic Paradox (HP). Few studies have evaluated if the HP exists in surgical patients. Our study aimed to examine postoperative complications between Hispanic and NHW patients undergoing low to high-risk procedures. MATERIALS AND METHODS: We conducted a retrospective cohort study analyzing adult patients who underwent high- intermediate- and low-risk procedures. The Healthcare Cost and Utilization Project California State Inpatient Database between 2006 and 2011 was used to identify the patient cohort. Candidate variables for the adjusted model were determined a priori and included patient demographics with the ethnic group as the exposure of interest. RESULTS: The median age for Hispanics was 52 (SD 19.3) years of age, and 38.8% were male (N = 87,837). A higher proportion of Hispanics had Medicaid insurance (23.9% vs. 3.8%) or were self-pay (14.2% vs. 4.5%) compared to NHW. In adjusted analysis, Hispanics had a higher odds risk for postoperative complications across all risk categories combined (OR 1.06, 95% CI 1.04 – 1.09). They also had an increased in-hospital (OR 1.38, 95% CI 1.14 – 1.30) and 30-day mortality in high risk procedures (OR 1.34, 95% CI 1.19–1.51). CONCLUSION: Hispanics undergoing low to high-risk surgery have worse outcomes compared to NHW. These results do not support the hypothesis of a Hispanic Paradox in surgical outcomes.